Incidence of complications in gynaecological laparoscopic surgeries: a prospective study from a single tertiary care centre - Thakur, Surekha; Wakhloo, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Laparoscopy is a widely utilized procedure in gynecology due to its minimally invasive nature, offering numerous benefits such as reduced postoperative pain, quicker recovery, and shorter hospital stays. However, as with all surgical procedures, complications may arise, particularly in more complex surgeries. This study aimed to evaluate the incidence of complications associated with gynecological laparoscopic surgeries performed at a single centre. Methods: A total 248 patients undergoing laparoscopic gynecological procedures at the centre during the study period were included. Informed consent was obtained from each patient, outlining the risks and the possibility of conversion to laparotomy if necessary. The study evaluated patient demographics, surgical history, body mass index (BMI), types of procedures performed, hospital stay durations, and the incidence of major and minor complications. Results: Mean age of 31.51±8.79 years. Diagnostic laparoscopy was performed in 39.51% of cases, while advanced procedures accounted for 27.01%. Complications occurred in 21 patients (8.47%), with major complications seen in 2 patients (0.80%) and minor complications in 12 patients (4.84%). Laparoscopic hysterectomy had the highest complication rate at 18.33%, and 6 patients required conversion to laparotomy. No complications were observed in diagnostic or minor surgeries. Conclusions: Laparoscopic surgery in gynecology is generally safe, with an overall complication rate of 8.47%, which aligns with reported literature. Complications were more frequent in complex procedures and in patients with previous abdominal surgeries. Continued improvements in surgical techniques and patient selection are essential for further reducing complication rates and enhancing surgical outcomes.